Clube de Ciências: Uma possibilidade para a Alfabetização Científica e Atitudes Científicas nos anos iniciais do Ensino Fundamental - Cogo, Thaís Cristina (2021)
The research of qualitative approach in Science Education aimed to understand how the development of investigative activities with students from the early years can enhance Scientific Literacy from the organization of a Science Club in a private school in Francisco Beltrao - PR city in order to develop investigative workshops and carry out activities with students. Twenty-two elementary school students participated in this research, of which 10 students were from the 3rd year and 12 belonging to the full-time education regime of the school, these being from the 1st to the 4th year. Teachers who teach or taught the science subject at school also participated in the research, totaling seven interviewees. The data were analyzed through Content Analysis, especially thematic analysis, by Laurence Bardin (1977). The priori categories sought to relate the dimensions of CA proposed by Leite (2015) and the scientific attitudes of the authors Pozo and Crespo (2009). Based on this foundation, the research proposed to understand, based on the analysis of the semi-structured interviews from the teachers and the data collected in the Science Club with the students (elaboration of drawings and narratives, besides the workshop audio and video records), how the investigative activities could promote Scientific Literacy. From the interviews content, subcategories related to the specificities of science teaching at school, teaching difficulties in this area and perspectives for the improvement of these limitations emerged. About the students, the data made it possible to understand that the investigative process allows them to relate the daily life with scientific knowledge; furthermore, the proposed relationship between the dimensions of Scientific Literacy and Scientific Attitudes made it possible to understand the students' representations about the science nature and attitudes towards science, scientific knowledge as which socio-scientific aspects and attitudes towards the science social implications. Through these categories of analysis, we understand that the relationship with socio-scientific aspects was the one with the greatest difficulty for promotion compared to the other two dimensions and scientific attitudes. In this way, we believe in the importance of developing investigative activities in science teaching for students in the early years of elementary school.